Strategi Pemasaran Online dan Kualitas Produk terhadap Minat Beli Konsumen pada Industri Fashion di Shopee - Novita Dwi Wardhani; Imron Rosyadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the effectiveness of online marketing strategies and evaluate the impact of product quality on consumer purchase intention in the fashion industry on the Shopee e-commerce platform. Along with the rapid development of the fashion industry and high digital competition, business actors are required to understand consumer preferences and provide quality products through targeted marketing. This research uses a quantitative approach with primary data collection through questionnaires distributed to respondents who are consumers of fashion products on Shopee. The data were analyzed using multiple linear regression, t-test, and F-test. The results showed that online marketing strategy partially has a positive and significant effect on consumer purchase intention (t-count 2.116 > t-table 1.984). Product quality also partially has a positive and significant effect on consumer purchase intention (t-count 2.964 > t-table 1.984). Simultaneously, both independent variables were proven to have a significant effect on consumer purchase intention. In conclusion, increasing consumer purchase intention in the Shopee fashion industry requires an optimal combination of attractive online marketing strategies, such as promotions and free shipping, alongside the provision of high-quality products that match the description.